Las figuras cómicas del mono y de los portadores de pintura corporal negra entre los nahuas prehispánicos y su transformación en la época colonial - Agnieszka Brylak (Journal de la Société des Américanistes)
The article aims to study the phenomena of humor and laughter in pre-Hispanic Nahua culture, focusing on two burlesque figures: the monkey and the beings with black body painting. It analyzes their function and their links with the laughable in sacred narratives and in the performative manifestations of the culture, such as religious festivals and public performances. Due to the presence of the same types—the ape and the black or devil—in medieval and Renaissance popular and carnivalesque culture, part of this study will briefly mention the transformation of pre-Hispanic jesters and their fusion with their European counterparts that occurred in colonial times in New Spain.